Information - the driving force behind development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Structural adjustment is resulting in rapid changes in management responsibility and power structures, not only in the ACP countries but all over the world. The changes are affecting everyone from the state to the private sector. Governments are...